The Unique Australian Flora, A Veritable Pandora's Pharmacopeia of Compounds with Therapeutic Biomedical Potential: Are the Chalcones the Geni in The Box? (Global Journal of Science Frontier Research, 2021)
The aim of this review was to highlight the unique biodiversity of the flowering plants and shrubs of Australia and their component chemicals that evolved during the separation of the Australian continent from Gondwanaland. The chemicals produced by these flowering plants provided protection ensuring the survival of the Australian flora which had to contend with often harsh Australian climatic conditions. The diversity of plant phytochemicals produced by these flowering plants reflects the unique diversity of the Australian Flora and these represent a Pharmacological goldmine. It was beyond the scope of this review to cover the full spectrum of these chemical compounds present in Australian plants instead we focused on the chalcones in this review. This compound has a special status in medicinal chemistry as a base intermediate for the synthesis of a large repertoire of polycyclic compounds that display anti-bacterial, antifungal, anti-viral and anti-tumour properties and these are thus of considerable interest in Biomedicine.
Keywords: phytochemicals; chalcones; polyphenolics; flavonoids; biomedicine; australian native plants.